2017
DOI: 10.3233/jad-170154
|View full text |Cite
|
Sign up to set email alerts
|

Specific Verbal Memory Measures May Distinguish Alzheimer’s Disease from Dementia with Lewy Bodies

Abstract: DLB patients had a better performance in VL than AD, but worse VF and recency effect. These specific measures of verbal memory could be used as cognitive markers in the differential diagnosis between these two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…For the immediate recall trial, the verbal learning (VL) index was calculated; it corresponded to the difference between the number of words recalled in trial 5 minus the number of words recalled in trial 1. 52 A total of 14 cognitive measures were analyzed.…”
Section: General Neuropsychological Examinationmentioning
confidence: 99%
“…For the immediate recall trial, the verbal learning (VL) index was calculated; it corresponded to the difference between the number of words recalled in trial 5 minus the number of words recalled in trial 1. 52 A total of 14 cognitive measures were analyzed.…”
Section: General Neuropsychological Examinationmentioning
confidence: 99%
“…However, individuals with AD do not always show reduced primacy effects compared to other clinical groups. For example, although primacy effects were similar, individuals with AD demonstrated increased recency effects on learning trials compared to individuals with dementia with Lewy bodies (DLB; Bussè et al, 2017) and compared to individuals with behavioral variant Frontotemporal dementia (bvFTD; Consonni et al, 2017). In addition, research has also demonstrated the ability to distinguish between mild and moderate AD from FTD, LBD, and VaD by analyzing the reduced recency effects observed in delayed recall trials in individuals with AD (Turchetta et al, 2018).…”
Section: Spe As a Tool To Distinguish Between Other Neurocognitive Di...mentioning
confidence: 99%
“…At the neuropsychological level, RAVLT performance (STR, learning, and DR) can discriminate among normal aging, mild cognitive impairment (MCI) and Alzheimer's disease (AD; Marra et al, 2000;Estévez-González et al, 2003;Goryawala et al, 2015;Bauer et al, 2018) and is a good independent predictor of dementia (Eckerström et al, 2013;Li et al, 2017). Moreover, RAVLT DR performance can discriminate AD from other dementias, such as the behavioral variant of frontotemporal dementia (Ricci et al, 2012) or dementia with Lewy bodies (Bussè et al, 2017). Therefore, the clinical use of the RAVLT to detect memory impairment is supported by the French social security system (ALQP006 CCAM).…”
Section: Introductionmentioning
confidence: 99%